Detailed reconstructions of India–Somalia Plate motion, 60 Ma to present: implications for Somalia Plate absolute motion and India–Eurasia Plate motion. Issue 3 (31st July 2021) - DeMets, C; Merkouriev, S
SUMMARY: We estimate India–Somalia Plate motion at 45 times since 60 Ma from ∼9000 crossings of Carlsberg and northern Central Indian Ridge magnetic reversals C1–C26 and numerous fracture zone crossings. The new rotations reveal at least seven significant spreading rate changes since ∼60 Ma, some previously unknown. The largest changes occurred before 46 Ma, when the forces acting on the India Plate evolved rapidly due to the transition from subduction to continent–continent collision between India and Asia and the influence of the Reunion hotspot plume on the India Plate. The new rotations reveal a gradual ∼50 per cent decline in Carlsberg Ridge spreading rates from 57 to 52.7 Ma, but an end to the decline at ∼53 Ma, when spreading rates surged rapidly by up to 100 per cent. From 52 to 46.7 Ma, Carlsberg Ridge spreading rates collapsed by ∼90 per cent, possibly defining a protracted transition to continental collision between India and Asia. Significant kinematic events since 46.7 Ma have included a ∼25 per cent spreading rate recovery from 42 to 40 Ma, ultraslow spreading from 38.6 to 33.2 Ma, a gradual rate doubling from 33 to 18 Ma, a ∼50 per cent slowdown from 18 to 13 Ma, and apparently steady motion since 13 Ma. The new rotations successfully predict Carlsberg Ridge abyssal hill orientations for seafloor ages of 48 to 42 Ma and 20 to 0 Ma and Central Indian Ridge fracture zone traces for seafloor ages of 43–16 Ma, constituting useful tests of the rotation accuracies at these ages. When corrected for the movement of India relative to the Capricorn Plate since 16 Ma, the new rotations also successfully restore magnetic lineations C13, C18, C20 and C21, and fracture zone segments from the Capricorn Plate onto their Somalia Plate counterparts. This further confirms the accuracies of our new rotations back to C21n.1o (47.8 Ma), and validates a ∼16 Ma start date for India–Capricorn Plate motion and published correction for India–Capricorn motion. Anticorrelated changes in India–Somalia and Antarctic–Somalia seafloor spreading rates from 37 to 18 Ma may be evidence that Somalia Plate absolute motion changed during this period, possibly triggered by Somalia's post-30-Ma detachment from the Arabian Peninsula or the kinematic effects of the Afar and/or Reunion mantle plumes on the Somalia Plate. New India–Eurasia rotations that we estimate from an updated global plate circuit predict convergence rates from 53 to 47 Ma that are ∼30 per cent faster than previous estimates and that decline ∼75 per cent by ∼38 Ma. Changes in India–Somalia and India–Eurasia rates correspond closely with recently described Tibetan deformation pulses, consistent with linkages between all three. A joint inversion of Carlsberg and southern Central Indian ridge magnetic reversal and fracture zone data, including a correction for movement of the Capricorn Plate relative to India, satisfactorily realigns the reconstructed magnetic lineations and fracture zones back to C23n.1n (50.7 Ma), but misfits some data by 100 km or more at earlier times. The misfits may be evidence for deformation within the IndoCapricorn and/or Somalia plates before 48 Ma or a misinterpretation of magnetic reversal and/or fracture zone data from times before 48 Ma.